Auralization Fundamentals of Acoustics, Modelling, Simulation, Algorithms and Acoustic Virtual Reality - Vorländer, Michael (RWTHedition, 2008)
"Auralization" is the technique of creation and reproduction of sound on the basis of computer data. With this tool is it possible to predict the character of sound signals which are generated at the source and modified by reinforcement, propagation and transmission in systems such as rooms, buildings, vehicles or other technical devices. This book is organized as a comprehensive collection of the basics of sound and vibration, acoustic modelling, simulation, signal processing and audio reproduction. Implementations of the auralization technique are described using examples drawn from various fields in acoustic's research and engineering, architecture, sound design and virtual reality.